Characterization of ctx-m-type extended-spectrum beta-lactamases (esbls) among enterobacteriaceae from a portuguese hospital - Amaral, Soraia Necho (2010)
Na última década tem-se assistido à disseminação de enzimas do tipo ctx-m em diversos países, determinando alterações significativas na epidemiologia das beta-lactamases de espectro alargado (bleA). A monitorização da disseminação de enterobacteriaceae produtoras de ctx-m em portugal foi efectuada em isolados clínicos recentes de um hospital português. blactx-m e iss associadas ao seu ambiente genético foram pesquisados por pcr. A elevada prevalência de variantes de ctx-m do grupo i confirma a mudança na distribuição dos tipos de bleA em portugal. During the last decade ctx-m enzymes have become widespread in several countries, causing a shift in the esbl epidemiology of specific areas. in order to monitorize the dissemination of ctx-m-producing enterobacteriaceae in portugal, we characterized esbl producers recovered from a portuguese hospital. blactx-m and specific iss and genes associated with blactx-m genetic environment were searched by pcr. Detection of a high occurrence of ctxm cluster i variants confirms a shift in esbl distribution towards ctx-m enzymes in portugal.